CONVIVIALITY IN ANTIOCH ON THE ORONTES THROUGH THE STUDY OF FUNERARY STELES DATING FROM THE ANTIQUITY - Evrim Güven (European Scientific Journal, ESJ, 2014)
The funerary steles at Antioch on the Orontes and its surrounding areas from the Antiquity reveal the most convivial aspect of the society. Such an atmosphere of conviviality is also described in ancient writings and brought to light by the excavations of Princeton University in the 1930s . However, it was particularly difficult to propound the contribution of the steles to the conviviality of the society with certitude by means of either their iconographical or epigraphical testimony. For, the steles that represent more vividly such a social aspect were dispersed among Turkey, the United States of America, France, Syria and Lebanon. Moreover, their records were almost not illustrated at all. Therefore, none of the researches carried out throughout the 20th century offered a comparative study between the particular evidence provided by the funerary steles and the extant data. Observing such deficiencies in the preliminary studies, we attempted to constitute a most complete and illustrated corpus of steles and to analyze it as a major component of our doctoral thesis87. We shall present certain outcomes of the researches we conducted to determine how the conviviality is conceived on the steles, the mosaics and urban planning. We will also indicate principal similarities and differences between the steles and mosaics (in particular the representations of banquet which demonstrate most concretely the convivial ambience).